Beneath the Dark Web: Excavating the layers of cybercrime's underground economy - Lusthaus, J (IEEE, 2019)
The Dark Web or DarkNet has attracted both considerable media and scholarly attention. This forms part of a broader tradition of analyzing relatively open cybercriminal marketplaces and forums. With the aid of data collected over a 7-year period, the focus of this paper is to help demarcate - beyond the Dark Web alone - all the layers within the world of profit-driven cybercrime. These include: 1) the top layer, which is the most open forums and marketplaces, whether Dark Web or otherwise; 2) the middle layer of more closely vetted forums; 3) the bottom layer of even smaller and more closed groupings; 4) the molten core, which is centered on the offline organization of cybercrime. The purpose of this analysis is to identify key aspects of the underground economy which warrant further scholarly attention, and to suggest possible approaches to engage with these subjects going forward.